The principle of individualizing. The analysis of the conception by Jan Duns Szkot - Surzyn, Jacek (Folia Philosophica, 2008)
The article discusses the conception of the principle of individuation by John Duns Scotus, which is one of the most interesting analyses of this problem in the period of scholasticism. Scotus ascribed the principle of individuation an autonomous positive being correlated within the scope of the combination of a truly existing thing with the common nature. Thereby, he shows an interesting aspect of the individualization perspective in a formal sense as „something” unrepeatable and ascribed to only one real being and immediately constituting its structure. The conception of the principle of individuation became the crucial problem in the 14th century and the point of view held by Scotus was a starting point for the discussions on that issue.